1998
DOI: 10.1073/pnas.95.24.14314
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of peptide antigens by mouse CD1 requires endosomal localization and protein antigen processing

Abstract: Mouse CD1(mCD1) molecules have been reported to present two types of antigens: peptides or proteins and the glycolipid ␣-galactosylceramide. Here, we demonstrate that a protein antigen, chicken ovalbumin (Ova), must be processed to generate peptides presented by mCD1 to CD8 ؉ T cells. The processing and mCD1-mediated presentation of chicken Ova depend on endosomal localization because inhibitors of endosomal acidification and endosomal recycling pathways block T cell reactivity. Furthermore, a cytoplasmic tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 35 publications
3
32
1
Order By: Relevance
“…However, if such cells are present, they alone are incapable of mediating AHR. Neither the iNKT cells nor the ␥␦ T cells appear to recognize OVA, although it is difficult to rule out this possibility entirely (37,38). Whether they recognize other components in the OVA preparation used for sensitization and challenge (e.g., LPS), autologous ligands induced by the treatment of the recipients, or no ligands at all remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…However, if such cells are present, they alone are incapable of mediating AHR. Neither the iNKT cells nor the ␥␦ T cells appear to recognize OVA, although it is difficult to rule out this possibility entirely (37,38). Whether they recognize other components in the OVA preparation used for sensitization and challenge (e.g., LPS), autologous ligands induced by the treatment of the recipients, or no ligands at all remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…How the mCII 707-721 structurally fits into this groove is not clear. Other studies have shown that a CD1d-restricted peptide can elicit a cellular immune response in vivo (17), leading the researchers to opine that intracellular murine CD1d might normally be associated with peptides and therefore peptide presentation may be a true physiologic function of murine CD1d (8).…”
Section: Discussionmentioning
confidence: 99%
“…An endogenous ligand, isoglobotrihexosylceramide, has been shown to be involved in NKT cell autoreactivity (6). In addition to the association of CD1d with the binding and/or presentation of self and exogenous lipid or glycolipids (6), early reports have also indicated peptidepresenting capacity of CD1d (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Later, a peptide from chicken ovalbumin carrying the same motif (p18) was also shown to bind to CD1d and elicit an immune response (13,14). However, even though peptide CD1d-reactive T cells have been reported in these studies, their frequency and role in the context of the immune response remains controversial.…”
mentioning
confidence: 94%